2020
DOI: 10.2147/dddt.s270185
|View full text |Cite
|
Sign up to set email alerts
|

<p>[6]-Gingerol Ameliorates Cisplatin-Induced Pica by Regulating the TPH/MAO-A/SERT/5-HT/5-HT<sub>3</sub> Receptor System in Rats</p>

Abstract: Purpose [6]-gingerol is a bioactive compound extracted from ginger, a traditional anti-emetic herb in Chinese medicine. Previous studies have demonstrated that [6]-gingerol can ameliorate chemotherapy-induced pica in rats, although the underlying mechanism has not been elucidated. This study is designed to investigate [6]-gingerol’s antiemetic mechanism focusing on the 5-hydroxytryptamine (serotonin, 5-HT) system by evaluating the synthesis, metabolism and reuptake of 5-HT, as well as the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 32 publications
(68 reference statements)
1
32
0
Order By: Relevance
“…Cisplatin causes both acute and delayed GI tract disorders (<24 and >24 hours after administration, respectively) [32]. Our results are consistent with those of prior studies in which cisplatin caused significant mucositis and pica in rats [8,[33][34][35]. Another study revealed that treatment with the probiotic mixture used in our study (Bifidobacterium brevis DM8310, Lactobacillus acidophilus DM8302, Lactobacillus casei DM8121, and Streptococcus thermophilus DM8309) alleviates 5-fluorouracil-induced mucositis in rats [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cisplatin causes both acute and delayed GI tract disorders (<24 and >24 hours after administration, respectively) [32]. Our results are consistent with those of prior studies in which cisplatin caused significant mucositis and pica in rats [8,[33][34][35]. Another study revealed that treatment with the probiotic mixture used in our study (Bifidobacterium brevis DM8310, Lactobacillus acidophilus DM8302, Lactobacillus casei DM8121, and Streptococcus thermophilus DM8309) alleviates 5-fluorouracil-induced mucositis in rats [26].…”
Section: Discussionsupporting
confidence: 91%
“…A preliminary study revealed that cisplatin significantly increased TPH1 mRNA expression, but not TPH2 and SERT mRNA expression, in ileal tissue [51]. Another study demonstrated that cisplatin increased TPH1 and TPH2 mRNA expression in the ileum and medulla oblongata, respectively, indicating that cisplatin accelerates 5-HT synthesis through upregulating TPH, but has no effect on SERT [34]. We found that cisplatin significantly increased TPH1 and TPH2 levels in the colon but did not affect the SERT level.…”
Section: Discussionmentioning
confidence: 53%
“…The neurotransmitter 5-HT is an important cholinergic transmitter secreted and synthesized by the chromaffin cells of the intestinal mucosa. It can improve intestinal permeability, increase intestinal osmotic pressure, increase water secretion, and promote intestinal peristalsis to play an important role in regulating gastrointestinal motility and gastrointestinal secretion function [ 14 ]. Studies have shown that the 5-HT transmission pathway is the key factor in the pathogenesis of chronic constipation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To better evaluate the antiemetic mechanism of ginger, the major monomer 6-gingerol is used as an approach in a cisplatin-induced pica model of rats. It was found that pretreatment with 6-gingerol significantly mitigated CINV through downregulating the synthesis and promoting the metabolism of 5-HT, as well as blocking 5-HT 3 R ( Cheng et al, 2020 ). Moreover, 6-gingerol also ameliorated microbiota disorders to alleviate cisplatin-induced kaolin intake in the pica model of rats, regulated gastrointestinal hormones, and promoted gastric emptying ( Feng et al, 2019 ; Zhang et al, 2021 ).…”
Section: Antiemetic Effect Of Traditional Chinese Medicinementioning
confidence: 99%
“…On one hand, unlike chemical drugs that only intervene in a single target, TCM has multiple components and interacts with multiple targets in treating diseases. For example, ginger and its active ingredients like gingerols are shown to prominently exert antiemetic effect by blocking 5-HT 3 R, NK-1R, and D 2 R as well as regulating gastrointestinal dysfunction ( Cheng et al, 2020 ; Tian et al, 2020 ). On the other hand, combining Xiao-Ban-Xia decoction (XBXD) and the 5-HT 3 R antagonist as the prophylaxis of CINV clinically not only increases the antiemetic efficacy on delayed vomiting but also reduces the adverse reactions of the 5-HT 3 R antagonist ( Ouyang et al, 2002 ; Liu, 2018 ).…”
Section: Introductionmentioning
confidence: 99%